Understanding self-esteem of institutionalized children through serial drawing - Leyesa, Marjorie Dominina L. (2006)
This exploratory study aimed to facilitate an understanding of institutionalized children's self-esteem through tests and evaluation and a creative approach in counseling intervention called Serial Drawing. A group of ten institutionalized children participants from 10 to 12 years underwent the serial drawing, a Jungian approach where drawings should be viewed in series over time. These drawings serve as an outlet for the child to release emotions, gain in touch with his feelings, and gain an understanding of the confusing events in his life. This study revealed that children in residential care have low levels of self-esteem that need to be addressed. Through non-directive counseling approach in serial drawing, self-esteem levels of institutionalized children slightly increased. Improvement in regard of themselves were also seen as evidenced by more confident manifestation of behaviors and by movement of painful into positive images at the end of the intervention.
Thesis (M.A. Guidance)--University of the Philippines, Diliman.
Keywords: Self-esteem in children -- Philippines; Children -- Institutional care -- Philippines; Art therapy for children -- Philippines